Functionalising and Preserving Blood Platelets for Biologically Targeted Gene Therapies - Al athram, Nairouz (2025)
Blood platelets possess the unique ability to target wounds or inflammatory sites and to initiate clotting to prevent bleeding in severe trauma. Platelets also play important roles in several disease processes such as cancer cell invasion and metastasis. In recent years gene therapy has become an accepted branch of advanced therapy, and the use of primary cells such as platelets, as gene or drug delivery systems offers many potential applications. Platelets and/or platelet mediated gene therapy could therefore have applications in cancer therapy, as well as after surgery due to their anti-inflammatory/regenerative abilities and could deliver novel genes and gene products if they are transfected with foreign DNA. However, to date, there is an imbalance between the requirement for platelets and their availability, due to their short shelf life and the absence of appropriate storage. Better methods for platelet preservation and non-viral methods for platelet transfection could therefore facilitate wider deployment of platelet-based therapeutics. This study aimed to examine the applicability of platelets as a delivery route for genetic cargo into cells, allowing for targeted cancer therapy. To accomplish this a cell-penetrating, peptide based non-viral vector that utilises glycosaminoglycan binding enhanced transduction (GET) was used to deliver plasmid DNA into human platelets. To evaluate whether plasmid DNA carrying the Gaussia luciferase gene was delivered into platelets using the GET-peptide system. Luciferase assays were performed and results demonstrated platelets and GET/DNA complexed together was able to transfect target cells. Adding thrombin to this formulation resulted in an increase in transfection efficiency and this enhancement was combined with an increase in platelet activation as measured using an antibody that recognises CD-62 labelled with FITC as an activation marker. Using a platelet adhesion assay, the binding of platelets to different types of cancer cells was investigated. Calcien-labelled platelets adhered to breast, bile duct, and colorectal cancer cell lines. Furthermore, exposure to platelets resulted in increased cancer cell migration in all of the tested cell lines. Analysis of bile duct cancer cells lines showed that platelet treatment also increased cell number over time and impacted cell cycle progression. These data highlight a concern with using platelets for cancer gene therapy, since platelets might increase cancer cell migration and proliferation as well as delivering potentially therapeutic molecules. To address this, exhausted platelets were prepared by treating the platelets with thrombin to induce their activation and then using centrifugation to collect the exhausted platelets. The adherence of exhausted platelets to cancer cells was shown to decrease by around 30%, and decreased effects on cancer cell migration. However, exhausted platelets had very little stimulatory effect on cancer cell metabolic activity when compared to resting platelets. Finally, the potential of trehalose as a platelet cryoprotectant was investigated. Measurement of metabolic activity using a presto-Blue assay showed that trehalose improves cryopreservation compared to a control lacking trehalose. To determine whether cargo loaded platelets can function in cargo delivery after cryopreservation, cargo delivery was measured before and after cryopreservation. Platelets cryopreserved before loading with cargo demonstrated lower efficacy compared to platelets loaded and then cryopreserved. This highlights the significant challenge in maintaining platelet functionality through the loading and cryopreservation process. In summary this work provides new insights into the possibility of using platelets as a delivery system as well as highlighting the need for designing and implementing effective techniques for preserving platelets and extending their shelf life.